ANALISIS TINGKAT PENGANGGURANaTERBUKAaDANaINDEKS PEMBANGUNAN MANUSIA TERHADAPaKEMISKINAN PROVINSIaSUMATERA UTARA - Abd Halim Dalimunthe Dalimunthe; M.Faqih Aldiansyah Aldiansyah; Khairani Tambunan Tambunan (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Poverty is a common problem in the Indonesian economy in the North Sumatra region, where poverty is a complex and multidimensional problem. The aim of this research is to analyze the impact of open unemployment for people aged 15 years and over and the Human Development Index on poverty in North Sumatra. The population data used is secondary data obtained from a trusted government agency, namely the Central Bureau of Statistics for North Sumatra Province. Data analysis from 2019 to 2021 uses a simple linear regression analysis technique. The test method uses a simple linear regression analysis technique with a tadan test to test the Coefficient of Determination using the IBM SPSS tool. The results of this study are that the open unemployment rate has no effect on poverty and is significant, while the Human Development Index has an effect on poverty and is significant.